2020
DOI: 10.15171/hpp.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a cognitive affective model of physical activity behavior

Abstract: Background: To empirically evaluate a cognitive affective model of physical activity. This bidirectional, cyclical model hypotheses that executive control processes directly influence habitual engagement in exercise and also directly subserve the exercise-induced affective response to acute exercise associated with future physical activity. Methods: The present study employed a one-week prospective, multi-site design. Participant recruitment and data collection occurred at two separate University sites (one in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…As such, if the behavior is regarded as valuable, people are likely to feel a positive affective response to the behavior, and ultimately this may facilitate future behavioral engagement [45] , [84] . These findings are in alignment with previous experimental work [85] , which demonstrated that greater performance on a cognitive task was associated with favorable affective response to exercise, and in turn, this positive affect was associated with promoting current and future PA behavior. Taken together, there may be utility in enhancing creativity to increase the perceived enjoyment of PA and the amount of PA.…”
Section: Discussionsupporting
confidence: 91%
“…As such, if the behavior is regarded as valuable, people are likely to feel a positive affective response to the behavior, and ultimately this may facilitate future behavioral engagement [45] , [84] . These findings are in alignment with previous experimental work [85] , which demonstrated that greater performance on a cognitive task was associated with favorable affective response to exercise, and in turn, this positive affect was associated with promoting current and future PA behavior. Taken together, there may be utility in enhancing creativity to increase the perceived enjoyment of PA and the amount of PA.…”
Section: Discussionsupporting
confidence: 91%
“…By calculating the dynamic changes of acceleration, the accuracy of the study on whether the audience is in an "enjoying state" has reached nearly 90%. Loprinzi et al [26] proposed a cognitive emotional model to assess physical activity based on experience and to evaluate the exercise habit and intensity of adults. The emotional changes can be seen after the acute exercise, and it is related on the exercise intensity and exercise cycle of the volunteers.…”
Section: Affective Computing Based On Sensor Networkmentioning
confidence: 99%
“…It positively affects brain functioning and affective-cognitive performance by involving neurotropic, neuroendocrine, neuropeptide, and neurotransmitter systems. This mechanism occurs as aspects of executive function are directly related to physical activity (Loprinzi et al, 2020). Exercise training enhances brain plasticity by boosting neurogenerative, neuroadaptive, and neuroprotective processes, according to neurobiological studies on the subject.…”
Section: Based On the Polyvagal Theory Proposed Bymentioning
confidence: 99%